2001
DOI: 10.1002/ijc.1214
|View full text |Cite
|
Sign up to set email alerts
|

Herceptest: Her2 expression and gene amplification in non-small cell lung cancer

Abstract: HER2 is an erbB/HER type 1 tyrosine kinase receptor that is frequently over-expressed in malignant epithelial tumours. Herceptin, a humanised mouse monoclonal antibody to HER2, is proven therapeutically in the management of metastatic breast cancer, significantly prolonging survival when combined with cytotoxic chemotherapeutic agents. Immunohistochemical studies suggest that non-small-cell lung cancer (NSCLC) tumours may over-express HER2. Our aim was to evaluate HER2 gene amplification and semi-quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0
1

Year Published

2002
2002
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 12 publications
(13 reference statements)
8
42
0
1
Order By: Relevance
“…Based on the clinical experience from the breast cancer studies, it might be of interest to focus on NSCLC patients with 3+ IHC results and/or those having tumours with gene amplification. Data from the current and other studies (Cox et al, 2001) show that these conditions seem to be limited to adenocarcinomas and LCC. Thus, the number of patients who might be candidates for trastuzumab treatment seems to be more limited in the NSCLC population than in the breast cancer population, and such prospective clinical trials in NSCLC will require multicenter studies.…”
Section: Molecular and Cellular Pathologysupporting
confidence: 54%
See 2 more Smart Citations
“…Based on the clinical experience from the breast cancer studies, it might be of interest to focus on NSCLC patients with 3+ IHC results and/or those having tumours with gene amplification. Data from the current and other studies (Cox et al, 2001) show that these conditions seem to be limited to adenocarcinomas and LCC. Thus, the number of patients who might be candidates for trastuzumab treatment seems to be more limited in the NSCLC population than in the breast cancer population, and such prospective clinical trials in NSCLC will require multicenter studies.…”
Section: Molecular and Cellular Pathologysupporting
confidence: 54%
“…Other studies, such as Hirashima et al (2001) and Cox et al (2001) also detected clustered amplification only in rare cases of NSCLC. Disomic status for chromosome 17 was only found in 16% of the NSCLC tumours included in our study.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 79%
See 1 more Smart Citation
“…The present study confirmed that the same phenomenon exists in clinical specimens, but no clear association between protein overexpression and polysomy of chromosome 17 could be confirmed. Cox et al 25 screened 344 NSCLCs for HER2 overexpression by IHC and found that only 4.3% of tumors overexpressed HER2. They further analyzed the 21 IHCpositive cases identified by FISH and reported that 3ϩ tumors possessed gene amplification but not 2ϩ or 1ϩ tumors, except 1 case of polyploidy.…”
Section: Resultsmentioning
confidence: 99%
“…In lung cancer cell lines, dosedependent growth inhibition occurred only in cell lines with cell-surface HER-2/neu expression Cox et al, 2001). HER-2 antibodies also mediate complement-dependent cytotoxicity and/or antibodydependent celular cytotoxicity (Lewis et al, 1993).…”
Section: Erbb-1 (Egfr) Inhibitorsmentioning
confidence: 99%